Angliškų daiktavardinių skolinių gramatinės giminės problema Šiaurės Amerikos lietuvių kalboje - Pažūsis, L. (Kalbotyra, 1978)
The aim of the present paper is to review the relative role of various determiners which are at play in gender assignment to loan nouns from American English (i. e. a language void of grammatical gender) after their importation into Lithuanian (i. e. a language having that category) spoken by immigrants in the USA and Canada.English personal masculine/feminine loan nouns receive Lithuanian genders according to the sex of their designation. The general rule for English dual gender nouns is that they become masculine, unless it is necessary to use the available native feminine gender markers (the necessity of using feminine forms is limited on account of sociolinguistic factors and the peculiarities of the recipient language). Exceptions showing a conflict between morphological and natural gender distinctions are due to the strong impact of formal determiners.The formal (phonetic) structure of the termination of the loanword plays an exceptionally important role not only in the classification of English inanimate loan nouns with the Lithuanian productive declension types, but also in gender assignment (the feminine is applied approximately to only one noun in seven). The validity of semantic gender determiners increases to a positive degree only when they are in conflict with the formal ones and either operate as decisive determiners or produce vacillation in gender assignment. American Lithuanian can supply a number of English loan nouns which take the gender of their semantic equivalents in the recipient language.